Enterprising Extremists - Crime, Religion, and the Business of Violence in Pakistan - Zafar, Rabia. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Daniel Drezner.; Committee: Ayesha Jalal, and H. Zeynep Bulutgil.; Keyword: South Asian studies.